2022
DOI: 10.3390/ijms231911826
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Homeostasis Regulates TLR4 Expression and Signaling in Mast Cells

Abstract: The endoplasmic reticulum (ER) is a dynamic organelle that responds to demand in secretory proteins by undergoing expansion. The mechanisms that control the homeostasis of ER size and function involve the activation of the unfolded protein response (UPR). The UPR plays a role in various effector functions of immune cells. Mast cells (MCs) are highly granular tissue-resident cells and key drivers of allergic inflammation. Their diverse secretory functions in response to activation through the high-affinity rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…One involves the UPR ER , detected as the splicing of XBP1 mRNA and upregulation of DDIT3 mRNA, along with the consequent activation of ER-resident CASP4, leading to the formation of GSDMD pores through the cleavage of GSDMD by active CASP4 and the translocation of the GSDMD N-terminal fragment to the cell membrane (Figure 1, left). Although the precise mechanism linking TLR4 signaling to UPR ER is not yet clear, several reports suggest that stimulation of TLR4 induces UPR ER , particularly the splicing of XBP1 mRNA [20][21][22][23].…”
Section: The Mechanism Of Gga-induced Cell Deathmentioning
confidence: 99%
“…One involves the UPR ER , detected as the splicing of XBP1 mRNA and upregulation of DDIT3 mRNA, along with the consequent activation of ER-resident CASP4, leading to the formation of GSDMD pores through the cleavage of GSDMD by active CASP4 and the translocation of the GSDMD N-terminal fragment to the cell membrane (Figure 1, left). Although the precise mechanism linking TLR4 signaling to UPR ER is not yet clear, several reports suggest that stimulation of TLR4 induces UPR ER , particularly the splicing of XBP1 mRNA [20][21][22][23].…”
Section: The Mechanism Of Gga-induced Cell Deathmentioning
confidence: 99%
“…One involves the UPR ER , detected as the splicing of XBP1 mRNA and upregulation of DDIT3 mRNA, along with the consequent activation of ER resident CASP4, leading to the formation of GSDMD pores through the cleavage of GSDMD by active CASP4 and the translocation of the GSDMD N-terminal fragment to the cell membrane (Figure 2, left). Although the precise mechanism linking TLR4 signaling to UPR ER is not yet clear, several reports suggest that the stimulation of TLR4 induces UPR ER , particularly the splicing of XBP1 mRNA [22][23][24][25].…”
Section: The Mechanism Of Gga-induced Cell Deathmentioning
confidence: 99%
“…Studies have shown that the intestine is the main site of damage caused by soybean antigenic protein in weaned piglets, which is manifested by shortened retention time of chyme, disturbed nutrient and mineral transport and absorption, intestinal villi atrophy, and impaired small intestinal barrier structure, which leads to diarrhea, growth inhibition, and even death. 6,7 However, maintenance of the intestinal barrier is closely linked to intestinal epithelial cell (IEC) homeostasis [integrity of tight junctions (TJs), immune responses, programmed cell death, and proliferation]. 8 IECs, which constitute barrier and messenger cells between the intestinal luminal and the host immune system, are highly susceptible to endoplasmic reticulum (ER) stress (ERS).…”
Section: Introductionmentioning
confidence: 99%
“…Animal growth performance correlates positively with intestinal barrier function, suggesting that an intact intestinal barrier is a key determinant of animal health and growth performance. Studies have shown that the intestine is the main site of damage caused by soybean antigenic protein in weaned piglets, which is manifested by shortened retention time of chyme, disturbed nutrient and mineral transport and absorption, intestinal villi atrophy, and impaired small intestinal barrier structure, which leads to diarrhea, growth inhibition, and even death. , …”
Section: Introductionmentioning
confidence: 99%